The Influence of Environmental and Social Sustainable Development Goals on Financial Performance with Green Innovation as a Moderating Variable in Banking Companies on the Indonesia Stock Exchange - Priyono, Hendro; Sadalia, Isfenti; Syahyunan (Indonesian Journal of Entrepreneurship and Startups, 2025)
This study aims to analyze the effect of environmental SDGs and social SDGs on the financial performance of banking companies listed on the Indonesia Stock Exchange during the period 2019–2023. In addition, this study examines the role of green innovation as a moderating variable in the relationship between SDGs disclosures and financial performance. The sample was selected using purposive sampling technique, resulting in 23 companies as research samples. The analytical method employed in this study is Moderate Regression Analysis (MRA). The results show that environmental SDGs have a negative effect on financial performance, while social SDGs have no significant effect on financial performance. Furthermore, green innovation has a negative and significant effect on financial performance. The findings also indicate that green innovation negatively and significantly moderates the relationship between environmental SDGs and financial performance, while positively and significantly moderating the relationship between social SDGs and financial performance. These findings imply that the implementation of sustainability practices and green innovation requires proper management to generate a positive impact on the financial performance of banking companies.